Manifestasi Klinis dan Protokol Pemeriksaan Fisik Terhadap Korban Plecehan Seksual - Insan Anshori Umma (Jurnal Medika Hutama, 2024)
Sexual harassment cases are often not taken seriously by the public or authorities because many do not cause physical marks. Physical examination of victims who have been sexually abused is an important aspect in the handling and protection of victims. Victims of violence or sexual harassment generally experience high pressure, depression and trauma. The purpose of this study was to determine the clinical manifestations and physical examination protocols for victims of sexual harassment. The method used in this study is to conduct a literature search in online databases such as PubMed and Google Scholar published in the last 10 years. The result is that sexual harassment can produce various negative impacts on victims, both physically and psychologically which are prolonged, by conducting a physical examination from head to toe systematically or called “Head to toe” can allow the examiner to find evidence. In addition, it is also important that we act with the safety, dignity and rights of the victim in mind. In conclusion, sexual harassment can cause several clinical manifestations to the victim both physically and psychologically and a physical examination can greatly assist victims of sexual harassment in finding evidence related to sexual harassment cases.